Exoenzimas em rações de frangos de corte - Carvalho, Carolina Magalhães Caires (2016)
The study aimed to evaluate performance, relative weight of the small intestine, digestibility and deposition of minerals in the bone of broilers supplemented with enzymatic complex (carbohydrases and phytase) in sorghum-based diets or sorghum and millet. In the experiments based of sorghum and sorghum and millet were used 912 day-old male and female Hubbard Flex chicks (50:50) were distributed in a completely randomized design in a 2x2 factorial arrangement (Feed Control base Sorghum (Contcs); FeedReducedbase Sorghum (RedS); Feed Control base sorghum + Enzymatic Complex (Contcs + Enz);. Feed reduced base sorghum + Enzymatic Complex (RedS + Enz) in the study of feed basis of sorghum and millet the design was similar (Feed Control base sorghum + millet ( ContSM); Reduced feed based on Millet + Sorghum (RedSM); Feed Control based Sorghum + Millet + EnzimaticComplex (ContSM + Enz); Reduced Feed base Sorghum+ Millet + Enzimatic Complex (RedSM + Enz). At 35 and 42 days of age were determined performance data: feed intake (CR), body weight (BW), feed conversion (FC), viability (VIAB), relative weight of the small intestine and deposition of minerals in the bone. The digestibility was evaluated sorghum grain size (crushed and whole) with and without exoenzimatico complex. They used 32 birds, eight birds per treatment, in periods from 17 to 21 (initial) and 31 to 35 days of age (fattening). The exoenzimático complex used in feed favored the weight gain results, feed conversion and bone mineralization when compared to a control diet not added to enzymes, demonstrating its effect on non-starch polysaccharides and phosphorus phytic present as anti-nutritional factors in these diets, increasing the digestibility and supply of metabolizable energy, essential amino acids, methionine and lysine and calcium and phosphorus for bone formation. It is concluded that a safe strategy for inclusion in feed is based on the reduction of energy levels, essential amino acids, methionine and lysine and calcium and phosphorus in the expected result of the constant activity of the enzymes of this exoenzimático complex.